PEMBELAJARAN BERBASIS STEM (SCIENCE ENGINEERING MATHEMATICS AND SCIENCE) UNTUK MENINGKATKAN KEMAMPUAN TEKNIK SISWA - Hadistia Siti Nuryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2021)
The purpose of STEM (Science, Technology, Engineering and Mathematics) in education is in line with the demands of the 21st century education, that is so that students have scientific and technological literacy seen from reading, writing, observing, and doing science, as well as being able to develop the competencies it has to apply in dealing with problems in daily life related to the science STEM (National STEM Education Center, 2014). Many STEM integration efforts revolve around engineering and design engineering as an impetus for learning science, mathematics, and technological content. The National Research Council Framework for Science Education K-12 (2012) articulates and discusses the role of engineering as a mechanism by which students can learn meaningful scientific concepts (Moore, et all 2014). This study aims to improve students' engineering ability. Explanatory survey method was used in this study to detect their conception deeply. The respondense or participants of this study was eleven graders from public vocational school in Lembang in Agribusiness course. The results of this study indicate that Lembang vocational school students experience an increase in students’ engineering ability in plant agribusiness subjects.